Reflections on Ten Years of USAID’s Experience with Political Economy Analysis and Thinking and Working Politically - Brinkerhoff, Derick; Cassidy, Marc (TWP CoP, 2023)
The global Thinking and Working Politically (TWP) Community of Practic e (CoP), the Washington DC TWP CoP, and USAID organised a webinar on 5 December 2022 to take stock of how USAID and its partners have used P EA to inform programme strategy, design and implementation, and suppor t TWP. This paper synthesises the key points arising from the webinar, including observations on the impacts, opportunities, challenges, and prospects for PEA/TWP to become more deeply adopted and sustained as a development methodology and approach across sectors. It starts by de fining key concepts. It then highlights insights from the discussions of the impact of the application of PEA and TWP principles across sect ors. The paper concludes by looking at progress achieved to date, as w ell as constraints and opportunities to increase the uptake of both th inking and working politically in USAID-sponsored programming.